ANALYSIS OF FACTORS CAUSING LOW DISCIPLINE AMONG STUDENTS IN ELEMENTARY AND JUNIOR HIGH SCHOOLS: A REVIEW FROM THE PERSPECTIVE OF TEACHERS AND STUDENTS - nazifa elisa elisa; Agus Lestari (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to analyze the factors contributing to the low level of student discipline in elementary and junior high schools from the perspectives of teachers and students. The research method used is descriptive qualitative, with data collected through semi-structured interviews involving an elementary school teacher, a junior high school teacher, and a junior high school student. The results indicate that internal factors such as student interest and emotions, as well as external factors such as family environment, school environment, peer influence, and educator attitudes significantly affect student discipline levels. Furthermore, various forms of disciplinary violations were identified, including truancy, tardiness, and inappropriate behavior both inside and outside the classroom. Strategies for improving student discipline involve setting clear rules, consistent enforcement, providing role models by teachers, and creating a positive classroom environment. By implementing these strategies consistently, it is expected that student discipline will improve, fostering a more effective learning atmosphere and supporting the development of responsible and independent student character.